Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species - Armas, Luis F. De; Díaz, René Barba; Barroso, Aylín Alegre (Zootaxa, 2017)
Some of the taxonomic characters originally argued for the Cuban monotypic genus Cubacanthozomus Teruel, 2007, are unsubstantial. Others were misinterpretations of drawings given in the original description of Schizomus rowlandi Dumitresco, 1973, the only source of taxonomic information on which Teruel (2007) based the new genus. Recently a new collection of this species was made in a small cave about 350 m from one of the caves mentioned in the original description: Cueva de Majana, Baracoa municipality, Guantánamo province. On the basis of new morphological evidence found during examination of two females and a male, both the genus Cubacanthozomus and its type-species are herein redescribed. Cueva de Majana is recognized as the true type locality of C. rowlandi, which male holotype was erroneously listed as being collected in a cave from central Cuba, 600 km away. Additional data are provided on the morphology, natural history and conservation status of C. rowlandi, which is now being proposed as an endangered species.